Foramen Magnum and Dental Osteometry of Balami, Uda, and Yankasa Breeds of Sheep - Atabo, Shaibu Mohammed; Umar, Abubakar Abubakar; Shehu, Sani Abdullahi; Abubakar, Adamu Abdul; Jaji, Alhaji Zubair; Oyelewo, Fatima Oyenike; Muazu, Tauheed Abubakar; Baso, Abdullahi; Palupi, Tantri Dyah Whidi; Rosyada, Zulfi Nur Amrina (Universitas Airlangga, 2023)
The increasing demand for animal protein, particularly meat, requires a thoughtful approach to selecting the type of meat-producing animal to achieve maximum yields. This is crucial to maintain food security. This study aimed to evaluate and compare some skull osteometries. A total of 60 each of Balami, Uda, and Yankasa sheep (30 adult males and 30 adult females) were used in this study. The skulls were macerated using a hot water technique. Then 7 parameters were measured using a digital Vernier caliper. The obtained data were analyzed using ANOVA (p < 0.05). The result of this study was that the mean foramen magnum height (FMH) was highest, medium, and lowest in the Balami (2.1 ± 0.1 cm), Uda (1.9 ± 0.1 cm), and Yankasa (1.8 ± 0.0 cm) breeds, respectively, and vice versa in the foramen magnum index (FMI). The foramen magnum width (FMW) was similar in Balami and Uda but higher than in Yankasa (1.8 ± 0.1 cm). The FMH, FMW, and FMI were similar within sexes of the same breeds in Balami, Uda, and Yankasa. The mean dental length (DL), oral palatal length (OPL), and length of the upper molar row (LUM) were highest and lowest in Balami and Yankasa, respectively, while the mean length of the upper premolar row (LUP) was highest and lowest in Balami and Uda, respectively. The (DL), (OPL), (LUM), and (LUP) were higher in males than females in Balami and vice versa in Uda and Yankasa. In conclusion, craniometric values, including foramen magnum and dental osteometry, of indigenous Nigerian sheep breeds were used to compare them to other breeds and among themselves. It could also guide oral surgery and assist in identifying sheep breeds through comparative study.